Identification of an essential Schizosaccharomyces pombe RNA homologous to the 7SL component of signal recognition particle. - Brennwald, P (1988)
We have cloned the gene encoding a novel small cytoplasmic RNA from the fission yeast Schizosaccharomyces pombe. Four lines of evidence support the idea that this RNA is a homolog of the 7SL RNA component of mammalian signal recognition particle (SRP), which targets presecretory proteins to the endoplasmic reticulum membrane. First, it shares limited but significant primary sequence homology with previously identified 7SL RNAs and can be folded into a similar secondary structure. Second, it possesses the 5' triphosphate characteristic of unprocessed RNA polymerase III transcripts, and moreover, it is the only fission yeast RNA in this size range with such a terminus. Third, its behavior in cell fractionation experiments suggests that it is part of a small ribonucleoprotein which forms salt-labile contacts with larger structures. Fourth, the particle containing S. pombe 7SL RNA resembles mammalian SRP in both size (11S) and affinity for DEAE-Sepharose. Disruption of the single-copy gene, designated slr1+, reveals that the RNA is indispensable for growth in fission yeast. This result is not surprising, since secretion is an essential cellular process.